Enteral Nutrition Safety and Outcomes of Patients with COVID-19 on Continuous Infusion of Neuromuscular Blockers: A Retrospective Study - Hasan M. Al-Dorzi; Reem Yaqoub; Reema Alalmaee; Ghafran Almutairi; Allulu Almousa; Leen Aldawsari (Journal of Nutrition and Metabolism)
Background. Intravenous infusions of neuromuscular blocking agents (NMBAs) and prone positioning are recommended for acute respiratory distress syndrome (ARDS) due to COVID-19. The safety of enteral nutrition (EN) during these treatments is unclear. This study assessed EN tolerance and safety during NMBA infusion in proned and nonproned patients with ARDS due to COVID-19. Methods. This retrospective study evaluated patients who were admitted to a tertiary-care ICU between March and December 2020, had ARDS due to COVID-19, and received NMBA infusion. We assessed their EN data, gastrointestinal events, and clinical outcomes. The primary outcome was gastrointestinal intolerance, defined as a gastric residual volume (GRV) ≥500 ml or 200–500 ml with vomiting. We compared proned and nonproned patients. Results. We studied 181 patients (mean age 61.2 ± 13.7 years, males 71.1%, and median body mass index 31.4 kg/m2). Most (63.5%) patients were proned, and 94.3% received EN in the first 48 hours of NMBA infusion at a median dose <10 kcal/kg/day. GRV was mostly below 100 ml. Gastrointestinal intolerance occurred in 6.1% of patients during NMBA infusion and 10.5% after NMBA discontinuation (similar rates in proned and nonproned patients). Patients who had gastrointestinal intolerance during NMBA infusion had a higher hospital mortality (90.9% versus 60.0%; p=0.05) and longer mechanical ventilation duration and ICU and hospital stays compared with those who did not. Conclusion. In COVID-19 patients on NMBA infusion for ARDS, EN was provided early at low doses for most patients, and gastrointestinal intolerance was uncommon in proned and nonproned patients, occurred at a higher rate after discontinuing NMBAs and was associated with worse outcomes. Our study suggests that EN was tolerated and safe in this patient population.